Revelation : a new translation with introduction and commentary - Koester, Craig R., 1953- (New Haven : Yale University Press, 2014)
In this landmark commentary, Craig R. Koester offers a comprehensive look at a powerful and controversial early Christian text, the book of Revelation. Originally written for Christian communities in Asia Minor, Revelation depicts scenes of cosmic conflict in which God, the creator of the world, overcomes the forces of destruction and makes all things new. This often misunderstood portion of the New Testament repeatedly surprises readers by warning that judgment is imminent, only to interrupt the visions of terror with messages of hope and redemption. Koester provides richly textured descriptions of the book's setting and language, making extensive use of Greek and Latin inscriptions, classical texts, and ancient Jewish writings, including the Dead Sea Scrolls. While Revelation has often been viewed as world-negating, this commentary focuses on its deep engagement with social, religious, and economic issues. It also addresses the book's volatile history of interpretation and its cultural impact over the centuries. The result is a groundbreaking study that provides powerful insights and sets new directions for the continued appreciation of this visionary religious text.
Secondary sources -- Greek and Latin authors -- Jewish and early Christian texts -- Inscriptions and papyri -- Revelation : a translation -- Introduction -- I. History of interpretation and influence -- II. Historical issues -- III. Social setting of Revelation -- IV. Literary aspects -- V. Rhetorical aspects -- VI. Text of Revelation -- Bibliography -- Notes and comments -- I. Title and introduction to the book -- II. First cycle : Christ and the seven assemblies (1:9-3:22) -- III. Second cycle : the seven seals (4:1-8:5) -- IV. Third cycle : the seven trumpets (8:6-11:18) -- V. Fourth cycle : the dragon, the beasts, and the faithful (11:19-15:4) -- VI. Fifth cycle : the seven bowls and the fall of Babylon (15:5-19:10) -- VII. Sixth cycle : from the beast's demise to new Jerusalem (19:11-22:5) -- VII. Conclusion to the book -- Introduction of modern authors -- Index of subjects.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050
Keywords: Bible. -- Commentaries; Bible; RELIGION -- Biblical Studies -- New Testament; Electronic books; Commentaries